Urgensi Pendidikan Thariqat Bagi Masyarakat Modern - Ya'cub, Mihmidaty (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
This article attempts to explain thariqah as the solution for modern society to reach the real happiness in life. That is to say, following the guidance of mursyid, doing or following their teachings, and stepping up the stages in thariqah will lead to the real happiness in life. This is very important to do since life nowadays has been so complex that human beings mostly tend to think that happiness has been gained when they have a lot of wealth; and having a lot of wealth does not necessarily lead to happiness. For this reason, thariqah offers the solution.